The new price of regional security today - Bakhtiyar Irismetov (Research Parks Publishers, 2021)
The article deals with the process of forming territorial and regional security today, including in Central Asia. At the same time, an analysis is made of the role of international organizations and international relations in ensuring all levels of security in general.